Design of Reversible Binary Half and Full Adder/Subtractor Using Reversible Gates - Arwa S.Bazmalah,; Noorfazila Kamal, (Progress in Engineering Application and Technology, 2022)
The power consumption in classical computers has grown to be a critical issue. Thus, quantum computers have become a promising alternative to classical computers for more processing power and lower energy consumption. Reversible gates are important for building the quantum computers. Reversible circuits have various applications, such as digital signal processing, optical computing, quantum computing, etc. The design and synthesis of reversible gates and circuits have grown in popularity and attracted the attention of many researchers. The adder and subtractor are important computation blocks for the structure of the Arithmetic Logic Unit (ALU). In this paper, a design of reversible binary half and full adders and subtractors using reversible logic gates is proposed. The TR (Thapliyal Ranganathan) and Peres gates are used to construct the reversible half adder and subtractor circuit. Meanwhile, the Double Peres Gate (DPG), Fredkin, and NOT gates are used to build the reversible 1-bit full adder and subtractor circuit. The designs are optimized in terms of number of gates, constant inputs, garbage outputs, and quantum cost. The truth table representation and the Binary Decision Diagram (BDD) synthesis method are used to represent and synthesize the circuits, respectively. The circuits are synthesized and simulated using the Verilog Hardware Description Language code and Xilinx ISE 14.7. The results show that the proposed designs achieve the lowest quantum cost in both half adder/subtractor and full adder/subtractor. As the half adder/subtractor has six quantum cost and the full adder/subtractor has nine quantum cost.